Analysis Self-Reflection of Prospective Teacher-Students on TPACK Ability Through Case-Based Learning Model - Suci Nurpratiwi (Universitas Muhammadiyah Mataram, 2021)
This study aims to analyze students' self-reflection on their Technological, Pedagogical, Content Knowledge (TPACK) abilities through a case-based learning model. The research was carried out at the State University of Jakarta, with the research subjects 41 students of the Islamic Religious Education study program who took the micro-teaching course. This type of research is qualitative, with data collection methods through observation, interviews, documentation, and distributing questionnaires. The results showed that the case-based learning model in the micro-teaching course could stimulate students' self-reflection ability. Self-reflection related to TPACK is students can find out their strengths and weaknesses in terms of TPACK. The results of student self-reflection show that technological, pedagogical, and content knowledge skills are very good, with a percentage above 80%. In comparison, the aspect that is still low is mastery related to technological content knowledge with an average percentage below 50%.